2011
DOI: 10.1002/ijc.25812
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐stromal therapy with imatinib inhibits growth and metastasis of gastric carcinoma in an orthotopic nude mouse model

Abstract: Recent studies have revealed that platelet-derived growth factor (PDGF) plays a role in promoting progressive tumor growth in several organs; however, whether PDGF plays such a role in gastric carcinoma is undetermined. We examined whether inhibition of PDGF receptor (PDGF-R) tyrosine kinase signaling by imatinib affects tumor growth and metastasis in an orthotopic nude mouse model of human gastric carcinoma. TMK-1 human gastric carcinoma cells were injected into the gastric wall of nude mice. Groups of mice (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…In addition, the orthotopic cancer model reflects a relevant site to assess therapeutic outcomes, avoiding the false-positive drug responses caused by other cancer models (19). Although the orthotopic gastric cancer model has been employed in previous studies (20)(21)(22), little attention has been paid to its direct use for in vivo longitudinal monitoring and drug evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the orthotopic cancer model reflects a relevant site to assess therapeutic outcomes, avoiding the false-positive drug responses caused by other cancer models (19). Although the orthotopic gastric cancer model has been employed in previous studies (20)(21)(22), little attention has been paid to its direct use for in vivo longitudinal monitoring and drug evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…A different method using drugs which inhibit stromal mediators of tumor cell growth was successfully used by Sumida et al [80] to impair the growth of xenografted human gastric carcinoma by blockade of PDGF-R signaling. These investigators demonstrated that carcinoma-associated stromal fibroblasts, pericytes and lymphatic endothelial cells expressed high levels of PDGF-R whereas carcinoma cells did not and treatment with high-dose imatinib and irinotecan in combination inhibited tumor growth and lymph node and peritoneal metastases by disrupting stroma-tumor signaling via this natural mediator.…”
Section: Diagnostic Prognostic and Therapeutic Implications Of Undermentioning
confidence: 99%
“…However, it is controversial whether systemically administrated MSCs can home to a target tissue and migrate into it. Some reports demonstrated that MSCs migrate towards inflammatory tissue [58] as well as cancerous tissue and may potentially be used for therapeutic purposes [49,59]; however, others showed that most of the cells were trapped in lymph nodes or the lungs and disappeared soon after injection [60]. This discrepancy could be partly explained by the difference of cell source such as bone-marrow or fat tissue and whether the cells were cultured or not cultured after isolation [61].…”
Section: Discussionmentioning
confidence: 99%